EMPOWERMENT OF THE WOMEN FARMERS GROUP THROUGH THE CORPORATE SOCIAL RESPONSIBILITY FUND OF STATE BANKING INSTITUTIONS IN MAGUWOHARJO SLEMAN, INDONESIA - Putra, Aditya Ananta; Senjawati, Nanik Dara (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
The development of Corporate Social Responsibility (CSR) has been increasing because it provides various benefits. One of the state-owned enterprises that implements the CSR program is PT. Bank Rakyat Indonesia (BRI) Tbk with the BRI Peduli program. This study examines the empowerment process of women farmer groups in Karangploso, Maguwoharjo, Depok sub-regency, Sleman, by utilizing the funds from the Corporate Social Responsibility BRI Peduli program. This study uses a qualitative approach with informant retrieval using purposive sampling procedures. The informants in this research are the women farmer group (KWT Mentari), the Chairperson, KWT Mentari Administrators, and the facilitators. The data sources in this study consist of primary and secondary data, using data collection techniques of observation, interviews, and documentation. The collected data were tested for validity by triangulation of sources. Data analysis was carried out using the Miles and Huberman model, which included stages of data collection, data reduction, data presentation, and conclusion. The results of this study indicate that the empowerment that occurs in the women farmer group (KWT Mentari) through the CSR BRI Peduli program has reached the stage of giving power.